Effectiveness of chemotherapy with/without radiotherapy for stage IVb esophageal squamous cell carcinoma: a population-based target trial emulation study - Yao-Hung Kuo; Chen-Yuan Lin; Yao-Ching Wang; Yo-Liang Lai; Yu-Cheng Kuo; Ji-An Liang; Chia-Chin Li; Chun-Ru Chien (Discover Oncology)
Abstract Background The role of radiation therapy in combination with systemic treatment for stage IVb esophageal squamous cell carcinoma (ESCC) is unclear. We aimed to investigate the effectiveness of primary chemoradiotherapy for these patients and compare it to that chemotherapy alone. Materials and methods In this retrospective cohort study, we adopted a target trial emulation framework to identify eligible patients in the Taiwan Cancer Registry diagnosed between 2011 and 2021. In the primary analysis, overall survival (OS) was the primary endpoint, whereas the incidence of esophageal cancer mortality was the secondary endpoint. Extensive supplementary analyses were also conducted. Results We included 5294 patients in the primary analysis and found that OS was significantly better for those treated with chemoradiotherapy (n = 5065) than for those treated with chemotherapy only (n = 229). The propensity score weighting adjusted hazard ratio of death was 0.46 (95% confidence interval 0.41–0.52, p < 0.0001). The secondary endpoint and supplementary analyses also favored the chemoradiotherapy group. Conclusion The OS of stage IVb ESCC patients treated with chemoradiotherapy was significantly better than that of patients treated with chemotherapy alone. The results of relevant ongoing clinical trials are eagerly awaited.